Music and lyrics [videorecording (Blu-Ray)] - Lawrence, Marc, 1959-; Grant, Hugh; Barrymore, Drew; Garrett, Brad, 1960-; Johnston, Kristen, 1967-; Scott, Campbell; Porter, Scott, 1979-; Bennett, Haley, 1988- (Castle Rock Entertainment ; Distributed by Warner Home Video, 2007)
Alex Fletcher is a washed-up 80s pop star who has been reduced to working the nostalgia circuit of county fairs and amusement parks. The charismatic and talented musician gets a chance at a comeback when reigning pop diva Cora Corman invites him to write and record a duet with her.